1 - Editorial: by Francis B. Nyamnjoh - Nyamnjoh, Francis B. (Africa Development, 2002)
Of late, CODESRIA has been experiencing problems publishing Africa Development regularly and has consequently accumulated a backlog of volumes. We sincerely apologise to our readership for failing to live up to their expectations, and pledge not only to clear the backlog, but also to restore the status of Africa Development as CODESRIA's flagship since 1976. To ease our task in this regard, we are now reinforced by a new editorial advisory board and an enriched pool of peer reviewers. In this context, we are appealing to all scholars and practitioners in the Social Sciences and Humanities to renew interest in the journal through their quality submissions on institutions and processes that impinge upon development in Africa. Proposals for guest-editorship on special themes are most welcome. Africa Development remains committed to its principal objective of providing a forum for the exchange of ideas among scholars of Africa from a variety of intellectual persuasions and various disciplines. The Publications and Communication page of the CODESRIA website (www.codesria.org) offers information on other journals working in conjunction with Africa Development to foster greater recognition and representation of African realities and perspectives in global knowledge production and consumption. In particular, we would like to draw your attention to our latest initiative, the Africa Review of Books, which offers a forum for critical presentation of books produced on Africa within and outside the continent. The Review is central to our goal of projecting interesting original works of art and science produced in Africa that might otherwise be lost on account of poor visibility. It is intended as a key barometer of trends in the study of Africa and a pacesetter for an all-round improvement in standards and quality. This issue of Africa Development (Vol XXVII, Nos. 1&2, 2002) continues with reflections on various aspects of some national economies, and touches as well on democratization, identity politics, education and the political economy of terrorism. The contributions are instructive in the questions they raise and in the substantiations they make.